Quercetin ameliorates epithelial-mesenchymal transition and inflammation by targeting FSTL1 and modulating the NF-κB pathway in pulmonary fibrosis - Lan, Yuejiao; Dong, Cuiting; Wu, Mingda; Yuan, Ruichen; Yang, Kunpeng; Yang, Zhen; Chen, Yang; Zhang, Jingbin; Qi, Bingxue; Lu, Xiaodan (Frontiers in Pharmacology, 2025)
BackgroundIdiopathic pulmonary fibrosis (IPF) is a progressive disorder characterized by chronic inflammation and pathological lung remodeling driven by excessive extracellular matrix deposition. While the flavonol quercetin exhibits established anti-inflammatory and antioxidant properties, its therapeutic mechanisms against IPF—particularly regarding epithelial-mesenchymal transition (EMT) and inflammation regulation via the follistatin-like 1 (FSTL1)/nuclear factor kappa B (NF-κB) axis—remain incompletely elucidated. This study therefore investigates quercetin’s capacity to mitigate pulmonary fibrosis through targeted modulation of the FSTL1/NF-κB pathway.MethodsA bleomycin (BLM)-induced pulmonary fibrosis mouse model and Transforming Growth Factor Beta 1 (TGF-β1)-induced EMT models in A549 and BEAS-2B cells were employed. The therapeutic effects of quercetin were assessed through H&E, Masson, Sirius red staining, immunofluorescence, quantitative real-time PCR (qRT-PCR), and Western blotting. The role of FSTL1 and NF-κB signaling in the anti-fibrotic effects of quercetin was evaluated using FSTL1 knockdown.ResultsIn vivo studies have shown that BLM-induced pulmonary fibrosis and inflammation significantly increased the deposition of extracellular matrix and the levels of interleukin-1 beta (IL-1β), monocyte chemoattractant protein-1 (MCP-1), and interleukin 6 (IL-6), all of which were markedly reduced by quercetin administration. In vitro experiments revealed that quercetin suppressed TGF-β1-induced EMT and inflammation. Importantly, FSTL1 knockdown diminished the anti-inflammatory and anti-EMT effects of quercetin.ConclusionQuercetin exerts its protective effects against pulmonary fibrosis by suppressing FSTL1 expression and modulating the NF-κB signaling pathway, thereby inhibiting both inflammation and EMT process.